PELATIHAN DETEKSI BORAKS PADA SAMPEL MAKANAN DI DESA KAMAL KECAMATAN ARJASA KABUPATEN JEMBER - Ayu Tri Agustin (Jurnal SADEWA, 2026)
Borax is a hazardous chemical substance that is prohibited from being used as a food additive due to its adverse effects on human health. However, in practice, borax is still found in several traditional food products. This community service activity aimed to increase the knowledge and skills of the community in Kamal Village, Arjasa District, Jember Regency, in detecting the presence of borax in food products circulating in their environment. The methods used included educational sessions on the health risks of borax and hands-on training on simple borax detection tests applied to selected food samples. Three types of commonly consumed food samples—bleng/puli, white tofu, and meatballs—were tested in this activity. The results showed that the bleng/puli sample tested positive for borax, while the white tofu and meatball samples showed negative results. This activity enhanced community awareness of the risks associated with borax in food and equipped participants with basic skills to independently perform preliminary detection. It is expected that this program will encourage greater vigilance and promote the selection of safe food for consumption.